2012
DOI: 10.3349/ymj.2012.53.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum C-Reactive Protein as a Prognostic Marker in Small Cell Lung Cancer

Abstract: PurposeElevated C-reactive protein (CRP) is associated with poor prognosis in several tumor types. The purpose of this study was to investigate serum CRP as a prognostic marker in small cell lung cancer (SCLC).Materials and MethodsThe pretreatment serum CRP level was measured in 157 newly diagnosed SCLC patients, and correlation between serum CRP level and other clinical parameters was analyzed. Multivariate analyses were performed to find prognostic markers using Cox's proportional hazards model.ResultsThe in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 39 publications
5
36
0
Order By: Relevance
“…Among subjects with an immune memory, anti-HB titers ≥10 mIU/mL were still persistent 1, 5, and 10 years after challenge in 91.3% (158 of 173), 77.3% (109 of 141), and 64.4% (38 of 59), respectively. 3,4 Similar to the study by Spradling et al, our results indicate that virtually all those vaccinated with residual anti-HBs titers (0.5-9.9 mIU/mL) have an immune memory to the HBV surface antigen (HBsAg). However, in our study, a higher proportion of those without residual anti-HBs showed an immune memory compared to those in the aforementioned study (94% vs 82%).…”
Section: Short-and Long-term Effects Of a Challenge Dose Of Hepatitissupporting
confidence: 89%
See 1 more Smart Citation
“…Among subjects with an immune memory, anti-HB titers ≥10 mIU/mL were still persistent 1, 5, and 10 years after challenge in 91.3% (158 of 173), 77.3% (109 of 141), and 64.4% (38 of 59), respectively. 3,4 Similar to the study by Spradling et al, our results indicate that virtually all those vaccinated with residual anti-HBs titers (0.5-9.9 mIU/mL) have an immune memory to the HBV surface antigen (HBsAg). However, in our study, a higher proportion of those without residual anti-HBs showed an immune memory compared to those in the aforementioned study (94% vs 82%).…”
Section: Short-and Long-term Effects Of a Challenge Dose Of Hepatitissupporting
confidence: 89%
“…Here, we present the response to a challenge dose in subjects with and without residual antibodies (0.5-9.9 or 0 mIU/mL) 5, 10, or 15 years after vaccination (Table 1), as well as the persistence of ≥10 mIU/mL anti-HB levels 1, 5, and 10 years following challenge-dose administration. 3,4 The criterion for the presence of immune memory was met by 99.1% (226 of 228) and 94% (79 of 84) of subjects with and without residual anti-HB levels, respectively. Among subjects with an immune memory, anti-HB titers ≥10 mIU/mL were still persistent 1, 5, and 10 years after challenge in 91.3% (158 of 173), 77.3% (109 of 141), and 64.4% (38 of 59), respectively.…”
Section: Short-and Long-term Effects Of a Challenge Dose Of Hepatitismentioning
confidence: 99%
“…Furthermore, in line with our previous results with mRNA, we show that combining serum levels of IL-6 with IL-8 gives superior prognostic information compared to these markers alone. Some prospective studies have also found associations between circulating cytokines with lung cancer outcome 9, 10, 12 , but few have investigated the association between circulating inflammatory markers and lung cancer survival in stage I disease. Our analyses were not corrected for multiple comparisons; however, the possibility for false discovery is reduced by the fact that it confirms other studies 8, 36 .…”
Section: Discussionmentioning
confidence: 99%
“…As nonspecific inflammatory markers, numerous studies found the elevation of pretreatment NLR and PLR to be independent poor prognostic factors for colorectal cancer, non-small cell lung cancer, gastric cancer, and pancreatic cancer [15][16][17][18]. Recently, Soojung Hong [19] and his colleague reported that the elevated pretreatment serum CRP level was associated with poor long-term prognosis for SCLC. However, serum CRP levels are not yet routinely evaluated as part of the preoperative assessment.…”
Section: Introductionmentioning
confidence: 97%